Implementasi Metode Bayani, Burhani, dan Irfani Dalam Pembelajaran Pendidikan Agama Islam - Suryani, Irma; Dewi, Eva; Anwar, Khairil (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In relation to the theory of knowledge (epistemology), Islam adopts various approaches to analyze its concepts and thoughts. Generally, there are three primary models within Islamic thought systems: Bayani, Burhani, and Irfani. Each of these models represents a distinct scientific perspective. In the context of Western epistemology, these approaches align with the concepts of Empiricism, Rationalism, and Intuitivism. This study employs a library research method, which involves collecting data and information from various library sources such as reference books, previous research findings, articles, notes, and relevant journals. The primary aim of this article is to provide a conceptual and methodological foundation for understanding and teaching Islamic Education (PAI), while also offering comprehensive insights for educators and students to explore the meanings and wisdom of Islamic teachings. The analysis reveals that PAI learning can provide students with a deep and holistic experience through the integration of these three epistemological approaches. The Bayani, Burhani, and Irfani paradigms create a learning environment that encourages balanced intellectual and spiritual exploration, fostering individuals who are intelligent, critical, and possess a profound understanding of Islamic teachings.